2010
DOI: 10.1111/j.1742-4658.2010.07671.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular metamorphosis in polcalcin allergens by EF‐hand rearrangements and domain swapping

Abstract: Polcalcins such as Bet v 4 and Phl p 7 are pollen allergens that are constructed from EF‐hand motifs, which are very common and well characterized helix–loop–helix motifs with calcium‐binding functions, as elementary building blocks. Being members of an exceptionally well‐characterized protein superfamily, these allergens highlight the fundamental challenge in explaining what features distinguish allergens from nonallergenic proteins. We found that Bet v 4 and Phl p 7 undergo oligomerization transitions with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Polcalcins are 9‐kDa calcium‐binding pollen proteins of unknown biologic function. While regular polcalcins contain two EF‐hand domains, several polcalcin‐related allergens with three or four EF‐hand domains were described . Polcalcins were shown to be minor albeit highly cross‐reactive allergens identified in pollen from diverse plant families (Fig.…”
Section: Ef‐hand Superfamilymentioning
confidence: 99%
“…Polcalcins are 9‐kDa calcium‐binding pollen proteins of unknown biologic function. While regular polcalcins contain two EF‐hand domains, several polcalcin‐related allergens with three or four EF‐hand domains were described . Polcalcins were shown to be minor albeit highly cross‐reactive allergens identified in pollen from diverse plant families (Fig.…”
Section: Ef‐hand Superfamilymentioning
confidence: 99%
“…Polcalcins are pollen-specific proteins containing two EF-hands highly conserved in a variety of dicot and monocot species (Rozwadowski et al 1999). Polcalcins are mainly studied as strong human allergens (Magler et al 2010), but immunolocalization in certain model species showed that they are abundant cytosolic low-Mr proteins located at or near the pollen tube surface (Rozwadowski et al 1999). Polcalcins bind calcium and undergo changes in conformation, thus, should display regulatory function and perhaps is involved in signal transduction pathways (Ledesma et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…3). We have also produced monomeric polcalcin mutants stabilized by an internal disulfide bridge, which stabilizes the monomer conformation, as described by Magler et al (41). When RBL-SX38 cells were sensitized with either HAPPIE1 or HAPPIE2, no significant degranulation was detected when stimulated either wild-type monomer or disulfidestabilized monomeric allergens (Fig.…”
Section: Native Polcalcin Dimers Trigger Rbl-sx38 Cell Degranulationmentioning
confidence: 96%
“…The family of polcalcin proteins have been shown to exist both as monomers and domain-swapped homodimers (41). Recombinantly expressed polcalcins can form monomers and intertwined dimers, and these oligomeric states can be separated using size-exclusion chromatography during the purification process (Supplemental Fig.…”
Section: Native Polcalcin Dimers Trigger Rbl-sx38 Cell Degranulationmentioning
confidence: 99%